MicroRNAs in maxillofacial bone modeling and remodeling: implications for malocclusion development and orthodontic treatment - Chen, Baike; Zhang, Yuxin; Liu, Ousheng (Frontiers in Cell and Developmental Biology, 2024)
Modeling and remodeling are essential processes in the development and refinement of maxillofacial bones. Dysregulated bone modeling during the developmental stage may lead to maxillofacial bone malformations and malocclusion. Bone remodeling under mechanical loading serves as the biological basis for orthodontic treatment. Although previous reviews have indicated the significance of microRNAs (miRNAs) in bone metabolism, their roles in orchestrating maxillofacial bone modeling and remodeling remain unclear. This review aims to discuss the mechanisms in which miRNAs regulate the morphogenesis and development of maxillofacial bones, as well as their implications for maxillofacial malformations and malocclusion. Moreover, miRNAs participating in maxillofacial bone remodeling and their impacts on cell mechanosensing are also summarized. Given the intricate interplay of cells and signaling pathways, exosomal miRNAs emerge as the orchestrators of the modeling and remodeling process. The diagnostic and therapeutic potentials of miRNAs are also highlighted in this review for future clinical applications.